The exercise of parental responsibility in Latin American migrant families under the Chile Crece Program - Grau Rengifo, María Olaya (2023)
We intend to analyze how migrant parents in Santiago de Chile mean their exercise of parental responsibility and examine how this exercise is perceived from the perspective of the professionals of the Chile Crece Contigo (hereinafter ChCC) system. For this, interviews were conducted with Latin American migrant families with children up to five years old, a discussion group and interviews with those in charge of the stimulation rooms of the Family Health Centers of the Metropolitan Region. Showing that migrant parents make decisions in relation to their children about what they consider to mean the proper exercise of parental responsibility, where the best interest of children prevails as motivation. On the other hand, that the support provided by the State in the exercise of parenting has different views from the perspective of parents, highlighting parental responsibility as a duty and a preferential privilege against the State and in this case against professionals of the ChCC on behalf of the same. Finally, there are tensions and challenges that would make it possible to complicate the treatment of parental responsibility from cultural diversity, such as the lack of time versus the desire to be present in parenting, which goes hand in hand with the tensions over co-responsibility; the use of violent discipline methods in parenting as an accepted practice; and finally, the offer of a parenting support system, in the face of the lack of intercultural competence in public policy.